2018
DOI: 10.4149/gpb_2018020
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training and dietary restriction affect PINK1/Parkin and Bnip3/Nix-mediated cardiac mitophagy in mice

Abstract: The aim of this study was to investigate the effects of exercise training and dietary restriction on cardiac PINK1/Parkin and Bnip3/Nix pathways involved in mitophagy. C57BL/6 mice were assigned to control (C), exercise training (T), dietary restriction (D) and exercise training + dietary restriction (TD) groups. T group undertook 10 weeks of swimming training. D group was subjected to 40% food reduction. TD group undertook the combination of exercise training and food reduction. Suspectable mitophagy autophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Nix, as a protein of autophagy receptor, recruits members of the Atg8 family to the injured mitochondria through its own LIR motifs, thereby resulting in the removal of the mitochondria (Schwarten et al, 2009). Secondly, the PINK1/Parkin pathway is a significant pathway mediating mitophagy, and the activation of this pathway is associated with a decrease in the membrane potential of mitochondria (Zhao et al, 2018). Some studies have shown that high expression of Nix can induce a decrease of the mitochondrial membrane potential, and then activate the PINK1/Parkin pathway to co-mediated mitophagy (McLelland et al, 2014;Gao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nix, as a protein of autophagy receptor, recruits members of the Atg8 family to the injured mitochondria through its own LIR motifs, thereby resulting in the removal of the mitochondria (Schwarten et al, 2009). Secondly, the PINK1/Parkin pathway is a significant pathway mediating mitophagy, and the activation of this pathway is associated with a decrease in the membrane potential of mitochondria (Zhao et al, 2018). Some studies have shown that high expression of Nix can induce a decrease of the mitochondrial membrane potential, and then activate the PINK1/Parkin pathway to co-mediated mitophagy (McLelland et al, 2014;Gao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the parameters of the exercise paradigm used in this study were not rigorous enough to exacerbate similar cardiovascular changes in PinK1 KO rats. There also is evidence that augmented mitochondrial function plays a role in exercise-related changes in mitophagy in cardiac tissue [73,74]…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
“…Bnip3 expression was significantly upregulated in the CR rat kidneys, suggesting mitophagy can be increased by CR while the expression of Binp3 decreased in high‐caloric condition that indicated possibility of preventing mitophagy in this condition. In another study, Zhao et al 52 . examined the effects of exercise training and DR on cardiac mitophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Bnip3 expression was significantly upregulated in the CR rat kidneys, suggesting mitophagy can be increased by CR while the expression of Binp3 decreased in high-caloric condition that indicated possibility of preventing mitophagy in this condition. In another study, Zhao et al 52 examined the effects of exercise training and DR on cardiac mitophagy. Eight-week-old male mice were given AL water and standard mouse food before being randomly allocated in one of three groups; control (nÀ8), exercise trained (n = 8, mice underwent swim training 5 days/week for 10 weeks), CR (n = 8 mice were fed 40% less calories than normal for 10 weeks), and exercise training + CR (T + CR) groups.…”
Section: Fasting or Calorie Restriction And Mitophagymentioning
confidence: 99%